Animal models in gastrointestinal alcohol research: a short appraisal of the different models and their results - Siegmund, Sören Volker; Haas, Stephan; Schneider, Alexander; Singer, Manfred V. (Best practice & research. Clinical gastroenterology, 2003)
Alcohol-related diseases of the gastrointestinal tract play an important role in clinical gastroenterology. However, the mechanisms and pathophysiology underlying the effects of ethanol on the organs of the digestive tract are not yet completely understood. Animal models represent an essential tool for investigating alcohol-related diseases because they give researchers the opportunity to use methods that cannot be used in humans, such as knockout technology. However, there is still a need for new animal models resembling the human condition, since for some alcohol-related diseases such as chronic alcoholic pancreatitis, the ideal animal model does not yet exist. In this chapter, we provide an overview of the most commonly used animal models in gastrointestinal alcohol research. We will also briefly discuss the current concepts of the pathophysiological mechanisms involved in acute and chronic alcoholic damage of the oesophagus, stomach, small and large intestine, pancreas and liver.